Incidence of Vascular Anomalies and Variants Associated with Unilateral Venous Pulsatile Tinnitus in 242 Patients Based on Dual-phase Contrast-enhanced Computed Tomography - Dong, Cheng; Zhao, Peng-Fei; Yang, Ji-Gang; Liu, Zhao-Hui; Wang, Zhen-Chang (Chinese medical journal, 2015)
Background：A comprehensive assessment of various vascular anomalies and variants associated with venous pulsatile tinnitus （PT） by radiography is essential for therapeutic planning and improving the clinical outcome.This study evaluated the incidence of various vascular anomalies and variants on the PT side and determined whether these lesions occurred as multiple or single entities.Methods：The dual-phase contrast-enhanced computed tomography images of 242 patients with unilateral venous PT were retrospectively reviewed.The vascular anomalies and variants on the symptomatic and asymptomatic sides were analyzed,and the incidences of anomalies or variants on each side were compared.The number of anomalies and variants on the symptomatic side in each patient was calculated.Results：（1） A total 170 patients （170/242） had more than one anomaly or variant on the symptomatic side,and 58 patients （58/242） had a single lesion on tomography.（2） There was a statistically significant difference in the incidence of dehiscent sigmoid plate （P =0.000）,lateral sinus stenosis （P =0.014）,high jugular bulb （P =0.000）,sigmoid sinus diverticulum （P =0.000）,jugular bulb diverticulum （P =0.000）,dehiscent jugular bulb （P =0.000）,and a large emissary vein （P =0.006） between the symptomatic and asymptomatic sides.（3） Dehiscent sigmoid plate （86.4%） was the most frequent lesion on the symptomatic side,followed by lateral sinus stenosis （55.8%）,high jugular bulb （47.1%）,sigmoid sinus diverticulum （34.3%）,jugular bulb diverticulum （13.6%）,dehiscent jugular bulb （13.6%）,large emissary vein （4.1%）,sinus thrombosis （1.2%）,and petrosquamosal sinus （0.8%）.Conclusions：Various vascular anomalies and variants occur more frequently on the venous PT side.Preliminary findings suggest that venous PT patients may have multiple vascular anomalies or variants on the symptomatic side.